163k views
2 votes
When simplifying 4x^3-10x^2+6x/2x^3+x^2-3x, what are the term(s) that can be cancelled

User Wenmin Wu
by
5.7k points

1 Answer

7 votes

Answer:

x can be cancelled

Explanation:

we are given


(4x^3-10x^2+6x)/(2x^3+x^2-3x)

Firstly, we will factor numerator and denominator

and then we can factor it


4x^3-10x^2+6x=2x(2x^2-5x+3)


4x^3-10x^2+6x=2x(2x+1)(x-3)

now, we can factor denominator


2x^3+x^2-3x=x(2x^2+x-3)


2x^3+x^2-3x=x(x-1)(2x+3)

now, we can replace it


(4x^3-10x^2+6x)/(2x^3+x^2-3x)=(2x(2x+1)(x-3))/(x(x-1)(2x+3))

we can see that

both terms are having x common

so, x can be cancelled

So,

x can be cancelled

User Diemacht
by
5.6k points